Microbiota of maize kernels as influenced by Aspergillus flavus infection in susceptible and resistant inbreds - Moore, Geromy G.; Chalivendra, Subbaiah; Mack, Brian M.; Gilbert, Matthew K.; Cary, Jeffrey W.; Rajasekaran, Kanniah (Frontiers in Microbiology, 2023)
Nearly everything on Earth harbors a microbiome. A microbiome is a community of microbes (bacteria, fungi, and viruses) with potential to form complex networks that involve mutualistic and antagonistic interactions. Resident microbiota on/in an organism are determined by the external environment, both biotic and abiotic, and the intrinsic adaptability of each organism. Although the maize microbiome has been characterized, community changes that result from the application of fungal biocontrol strains, such as non-aflatoxigenic Aspergillus flavus, have not. In this study, we silk channel inoculated field-grown maize separately with a non-aflatoxigenic biocontrol strain (K49), a highly toxigenic strain (Tox4), and a combination of both A. flavus strains. Two maize inbreds were treated, A. flavus-susceptible B73 and A. flavus-resistant CML322. We assessed the impacts of A. flavus introduction on the epibiota and endobiota of their maize kernels and found that the native microbial communities were significantly affected, irrespective of genotype or sampled tissue. Overall, bacteriomes exhibited greater diversity of genera than mycobiomes. The abundance of certain genera was unchanged by treatment, including genera of bacteria (e.g., Enterobacter, Pantoea) and fungi (e.g., Sarocladium, Meyerozyma) that are known to be beneficial, antagonistic, or both on plant growth and health. Beneficial microbes like Sarocladium that responded well to A. flavus biocontrol strains are expected to enhance biocontrol efficacy, while also displacing/antagonizing harmful microbes.